Program Pemberdayaan Masyarakat melalui Pemanfaatan Limbah Mebel sebagai Sarana Peningkatan Soft Skill dan Hard Skill Mahasiswa - Cynthia Permata Sari; Nabila Aiko Larasati Ichsani; Azizan Ananda Salviano; Umianah Nur Assadah; Mutiara Oktavia Ramadhani; Lathifah Nur Rohmah; Salma Syafiqoh; Amelia Yulian Sari; Muhammad Syahrul; Raya Falluza Arifin (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
Community empowerment programs are an effective strategy for linking the need to develop student competencies with the need to solve community problems. Students are required not only to have hard skills relevant to their field of study, but also soft skills such as communication, teamwork, leadership, and problem-solving. Universities often do not provide learning spaces that offer direct practical experience. Through experiential learning, community empowerment programs provide opportunities for students to engage in socialization, training, mentoring, and field practice with the community. This involvement allows students to apply theory in a real-world context while developing interpersonal and professional skills